Lexical cohesion in the reading texts of Infotech" textbook and implications for teaching English for it and computer learners - Mai, Thành Hạnh (ĐHNN, 2017)
The paper consists of three main chapters. Chapter I is a review of relevant theories, based on which the theoretical background of the study is established. Chapter II analyzes lexical cohesive devices in texts of Infotech course. Finally, Chapter III proposes some suggestions to obtain achievements in teaching and learning ESP reading and vocabulary, particularly at Hanoi Institute of Technology.